2016
DOI: 10.1039/c6cp05251g
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of step-edge barrier crossing of para-sexiphenyl on the ZnO (101̄0) surface

Abstract: Mass transport processes of conjugated organic molecules (COMs) on inorganic surfaces are essential elements in thin film deposition for hybrid optoelectronic devices. Defects and in particular surface step-edges dictate the molecular nucleation and growth morphology, which itself determine many physical properties of the resulting hybrid interface. Here, we explore the detailed molecular kinetics and transport rates of a single physisorbed para-sexiphenyl (p-6P) molecule crossing a step-edge (a "hetero-Ehrlic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 69 publications
1
12
0
Order By: Relevance
“…It is clear that the ES effect is a common feature in the energy surface landscape. The evidence for its existence is found experimentally [15][16][17][18][19][20] or by ab initio calculations [23][24][25]. Moreover, it was shown that the type of ES can be controlled by appropriate step passivation.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…It is clear that the ES effect is a common feature in the energy surface landscape. The evidence for its existence is found experimentally [15][16][17][18][19][20] or by ab initio calculations [23][24][25]. Moreover, it was shown that the type of ES can be controlled by appropriate step passivation.…”
Section: Introductionmentioning
confidence: 90%
“…A kinetic Monte Carlo modeling study by Leal et al [22] was performed to test this idea, and it showed that mounded morphologies can be obtained even with a small barrier while self-affine growth is obtained in the absence of an explicit step barrier. The step height-dependent ES and step-edge crossing mechanisms of the organic molecule on a ZnO surface were studied [23], employing atomistic MD simulations and mean first passage time theory. Additionally, Xiang and Huang [24] performed the density functional theory-based ab initio method to obtain ES values for various step heights on different Cu terminations.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in configurational entropy associated with inter-ring torsion helps the p-6P to reduce the free energy barriers for surface diffusion, similarly as observed for the crossing of an atomic surface step-edge barrier. 39,40 In Fig. 6 a), b) and c) we plot the two-dimensional probability distributions P (x, y)…”
Section: Free Energy Landscapes For the Diffusion On The Surfacementioning
confidence: 99%
“…The coupling between the different degrees of freedom of adsorbed molecules is a phenomenon already observed and characterized for other molecular adsorbates. 39,41…”
Section: Angular Motion and Rotational Diffusion On The Surfacementioning
confidence: 99%
“…This is even more the case for systems of conjugated organic molecules (COM). In contrast to most atomic systems or systems of nearly spherical organic molecules like fullerene C 60 , elongated organic molecules like diindenoperylene, p-sexyphenyl (6P), the perylene derivative PTCDI-C 8 or pentacene are known to generally in-teract anisotropically with each other when adsorbed on both, organic and inorganic substrates [34,37,39,40,[66][67][68][69][70][71]. Therefore one expects rather complex cluster shapes and corresponding changes in the cluster density, cluster size distribution and the coalescence behavior in the sub-monolayer growth regime as compared to atomic systems.…”
Section: Introductionmentioning
confidence: 99%